Holiday dinner (left to right - counterclockwise) William J. Cromie, Bert Crary, Walter Boyd, Ed Robinson, Hugh Bennett - Cromie, William J. (Byrd Polar Research Center, The Ohio State University, 1957)
Credit: William J. Cromie